1988
DOI: 10.1073/pnas.85.11.3683
|View full text |Cite
|
Sign up to set email alerts
|

ATP-independent DNA strand transfer catalyzed by protein(s) from meiotic cells of the yeast Saccharomyces cerevisiae.

Abstract: An activity that catalyzes the transfer of a strand from a duplex linear molecule of DNA to a complementary circular single strand can be detected in crude extracts from mitotic and meiotic cells of the yeast Saccharomyces cerevisiae by adding yeast single-stranded DNA binding proteins. This DNA strand-transfer activity increases >15-fold during meiosis in MATa/MATa diploids prior to the detection of a 100-to 1000-fold increase in homologous chromosomal recombination. No increase is observed in MATa/MATa or MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 15 publications
1
35
0
Order By: Relevance
“…PPR2 is not an essential gene, and disruption mutants are characterized by sensitivity to nucleotidedepleting drugs such as 6-azauracil and mycophenolic acid (Exinger and Lacroute 1992). Such mutants also exhibit some effects on stationary phase morphology (Christie 1995), a resistance to oxidative damage (Seidel 2002), a possible effect on meiotic recombination (Sugino et al 1988), and a sensitivity to microtubuledestabilizing drugs (Malagon et al 2004).…”
mentioning
confidence: 99%
“…PPR2 is not an essential gene, and disruption mutants are characterized by sensitivity to nucleotidedepleting drugs such as 6-azauracil and mycophenolic acid (Exinger and Lacroute 1992). Such mutants also exhibit some effects on stationary phase morphology (Christie 1995), a resistance to oxidative damage (Seidel 2002), a possible effect on meiotic recombination (Sugino et al 1988), and a sensitivity to microtubuledestabilizing drugs (Malagon et al 2004).…”
mentioning
confidence: 99%
“…Previously, we have described the partial purification of strand exchange activities, termed recombinase fractions, from the human B lymphoblastoid cell line RPMI 1788 (Hsieh et al 1986), HeLa cells (Hsieh and Camerini-Otero 1989), and Drosophila melanogaster embryos (Eisen and Camerini-Otero 1988). DNA strand exchange or pairing activities from mitotic and meiotic cells of Saccharomyces cerevisiae (Kolodner et al 1987;Sugino et al 1988;Halbrook and McEntee 1989), Drosophila melanogaster embryos (McCarthy et al 1988), and human cells (Fishel et al 1988) have been reported by others.…”
mentioning
confidence: 99%
“…Each step may be carried out by an enzyme but it is possible that a cell may have two enzymes for the same steps as a safeguard. Also, the entire recombination process is operated by multienzymatic processes, as suggested by the presence of both ATP-dependent recA-like protein (m-rec) (1) and ATP-independent recA-like protein (mAi-rec) (14,15) in meiotic cells and the presence of meiotic recombination enzymes in meiotic cells and somatic recombination enzyme in somatic cells (1). These observations strongly support the presence of a multi-system functioning in various types of DNA recombination.…”
Section: Resultsmentioning
confidence: 65%